Green Product, Green Corporate Image, and Green Customer Loyalty at Hotel Indigo Bali Seminyak Beach - Dewi, Ni Luh Putu Utari; Sagitarini, Luh Linna; Winia, I Nyoman; Mataram, I Gusti Agung Bagus (Jurnal Bali Membangun Bali, 2023)
Purpose: This study aims to analyze the effect of the application of green product quality and green corporate image on green customer loyalty at Hotel Indigo Bali Seminyak Beach. Research methods: The data collection methods used are observations, interviews, questionnaires, and literature studies. The respondents in this study were 50 guests who stayed at Hotel Indigo Bali Seminyak Beach using the method of determining purposive sampling or sampling based on certain characteristics. The data analysis techniques used are descriptive qualitative and multiple regression analysis. A validity and reliability test was carried out on the questionnaire distributed to the respondents. Result and discussion: Based on the results of the t test that has been carried out, it was concluded that the two partially free variables have a positive influence on green customer loyalty at Hotel Indigo Bali Seminyak Beach. Green product quality is more dominant in affecting green customer loyalty compared to green corporate image because in reality guests staying at the hotel look more at how the quality of products or services offered by the hotel so that guests can decide to buy the product continuously. Implications: Green product quality and green corporate image together or simultaneously have a positive and significant effect on green customer loyalty.